THE ROLE OF ENGLISH SONGS IN SHAPING STUDENT MOTIVATION AND MOOD: A THEMATIC STUDY OF ENGLISH EDUCATION STUDENTS IN THE 2021–2022 ACADEMIC YEAR AT AL-QOLAM UNIVERSITY - Ainur Rohmah; Joko Wibowo (As-Sulthan Journal of Education, 2025)
In today's digital age, music, especially English songs, has become an integral part of students' lives. This study was conducted to address the lack of research that highlights the role of songs not only as a linguistic tool but also as a motivator and mood regulator in English language learning. Most previous studies have emphasized cognitive aspects; this research seeks to fill the gap by focusing on the affective dimension. The purpose of this study is to explore how English songs influence the motivation and mood of students in the English Education Program, class of 2021–2022 at Al-Qolam University, and to examine the conscious and unconscious use of songs as learning strategies. The study employed a qualitative method with thematic analysis by Braun & Clarke. Data collection was conducted through open-ended questionnaires and interviews. The findings indicate that English songs significantly enhance students’ motivation, improve mood, enrich vocabulary and pronunciation, and support autonomous and flexible learning. These findings suggest that songs can serve as an effective, enjoyable, and emotionally engaging learning tool for today's learners.